(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the teaching of chemistry, modern technologies, in particular, streaming technologies and virtual reality (VR) laboratories, play an important role in making the educational process more effective and interesting. These technologies allow students to more easily understand complex concepts of chemistry and perform practical experiments in a virtual environment.